2020
DOI: 10.1152/ajpgi.00232.2019
|View full text |Cite
|
Sign up to set email alerts
|

The IBD-associated long noncoding RNA IFNG-AS1 regulates the balance between inflammatory and anti-inflammatory cytokine production after T-cell stimulation

Abstract: The inflammatory bowel diseases (IBD) are a complex set of chronic gastrointestinal inflammatory conditions arising from the interplay of genetic and environmental factors. This study focuses on noncoding RNA transcripts as potential mediators of IBD pathophysiology. One particular gene, interferon γ-antisense 1 ( IFNG-AS1), has been consistently observed to be elevated in the intestinal mucosa of patients with actively inflamed IBD versus healthy controls. This study builds on these observations, demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Specific over-expression of IFNG-AS1 in T cells has led to significant enhancement of inflammatory cytokines, while attenuation of production of anti-inflammatory cytokines. Media from IFNG-AS1-overexpressing T cells has induced a potent inflammatory response in primary human peripheral blood mononuclear cells (PBMCs) ( 72 ). Lnc-ITSN1-2 is another lncRNA that affect T cells differentiation.…”
Section: Lncrnas and T Cell Regulationmentioning
confidence: 99%
“…Specific over-expression of IFNG-AS1 in T cells has led to significant enhancement of inflammatory cytokines, while attenuation of production of anti-inflammatory cytokines. Media from IFNG-AS1-overexpressing T cells has induced a potent inflammatory response in primary human peripheral blood mononuclear cells (PBMCs) ( 72 ). Lnc-ITSN1-2 is another lncRNA that affect T cells differentiation.…”
Section: Lncrnas and T Cell Regulationmentioning
confidence: 99%
“…Studies have shown that lncRNA IFNG-AS1, also known as Tmevpg1, regulates the production of IFN-γ [45]. For example, Carl Robert Rankin et al verified IFNG-AS1 promotes the production of IFN-γ, thus exacerbating inflammatory bowel disease (IBD) [46] and Juan Wang et al found TMEVPG1 enhances the immune response of Th1 cells in patients with Sjogren syndrome [47]. In addition, a large number of other studies have shown that IFNG-AS1 enhances the immune response of Th1 and is associated with autoimmune diseases such as Multiple sclerosis (MS) and Hashimoto's Thyroiditis (HT) [48,49].…”
Section: Effector Functionsmentioning
confidence: 99%
“…There is a positive link between IFNG-AS1 over-expression and the crucial inflammatory cytokine IFNG expression in immune cells 99 . Moreover, Rankin et al 100 illustrated that the IFNG-AS1 gene is located beside the inflammatory cytokine IL-22 gene and extensively regulates the proinflammatory cascade. IFNG-AS1 may promote the effects of Th1 cytokines (IFNG, IL-2) and reduce the effects of Th2 cytokines (IL-10, IL-13) through an MLL/ SET1 mechanism 100 .…”
Section: Ifng-as1mentioning
confidence: 99%
“…Moreover, Rankin et al 100 illustrated that the IFNG-AS1 gene is located beside the inflammatory cytokine IL-22 gene and extensively regulates the proinflammatory cascade. IFNG-AS1 may promote the effects of Th1 cytokines (IFNG, IL-2) and reduce the effects of Th2 cytokines (IL-10, IL-13) through an MLL/ SET1 mechanism 100 . Overall, lncRNA IFNG-AS1 is a potential target for treating patients with colitis.…”
Section: Ifng-as1mentioning
confidence: 99%